The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.5120/11627-7099
|View full text |Cite
|
Sign up to set email alerts
|

Performance Comparison between TCP Sack and TCP Vegas using NS-2 Simulator

Abstract: In this paper, two TCP variants are compared in different scenario. Transmission Control Protocol (TCP) is a reliable, end-to-end transport protocol which is most widely used for data services and is very efficient for wired networks. It also performs well in wireless networks. It is the backbone protocol of most of the internet based applications. Our analysis is on performance of TCP variants. In this paper we carry out performance study of TCP Sack and TCP Vegas to be able to classify which variant of TCP p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…"Performance Comparison between TCP Sack and TCP Vegas using NS-2 Simulator" [3] This paper showed the comparison between two TCP Variants that is TCP SACK and TCP VEGAS to classify out of which one performs better than each other and the results showed that TCP Vegas is much better than TCP SACK in terms of throughput.…”
Section: B Design Of Tcp Congestion Control Techniques By Router Assmentioning
confidence: 99%
“…"Performance Comparison between TCP Sack and TCP Vegas using NS-2 Simulator" [3] This paper showed the comparison between two TCP Variants that is TCP SACK and TCP VEGAS to classify out of which one performs better than each other and the results showed that TCP Vegas is much better than TCP SACK in terms of throughput.…”
Section: B Design Of Tcp Congestion Control Techniques By Router Assmentioning
confidence: 99%
“…In [1], it is explained that this window serves to thwart the communication link between the communicating nodes from getting overwhelmed by traffic. Overwhelmed networks lead to packet losses, which according to [2] may be caused by malicious packet dropping and link error.…”
Section: Introductionmentioning
confidence: 99%
“…Infrastructure networks have a central controlling device which is responsible for performing all the functions. Where as in the infrastructure less networks, there present no central controlling device and the nodes itself are responsible for performing the function [2]. Mobile ad hoc network comes under the category of infrastructure less network in which there present no pre existing networks.…”
Section: Introductionmentioning
confidence: 99%